(untitled) (Global Journal of Medical Research, 2015)
In the past century, colorectal surgeons considered a cleansed and empty bowel, a pre-requisite for a safe colonic and rectal resection and anastomosis. Also during this period, acute left colonic obstruction in an unprepared colon, could only be resected and primarily anastomosed if a proximal diverting colostomy was instituted. Tradition has held that an unprepared colon, poses an unacceptable high rate of failure of the anastomosis to heal. But recent evidence from Europe and other centres of the world have proven this surgical dogma to be incorrect. The purpose of this study is to report our experience with a single-staged resection and primary anastomosis of acute left colonic obstruction, without bowel preparation or a diverting colostomy.